Produção de celulose bacteriana de alta absorção utilizando resíduo de processamento de caju - Guimarães, Darlyson Tavares (2023)
Bacterial cellulose (BC) is a nanostructured biopolymer that has been widely requested due to its intrinsic characteristics of high crystallinity, hydrophilicity and thermal and mechanical resistance. Komagataeibacter bacteria are the main potential producers of BC, but their limiting factor for large-scale production are the high costs involved, mainly those related to the culture medium, which represent up to 65% of the total production cost. A sustainable alternative to make this process viable is the use of agro-industrial by-products as a source of carbon and nitrogen. In this study, residual cashew juice effluent (MRC) was evaluated for BC production by Komagataeibacter xylinus ATCC 53582, Komagataeibacter xylinus ARS B42 and Komagataeibacter hansenii ATCC 23769, compared to the synthetic medium HS (MHS). The bioprocess was carried out in static system in BOD oven, between 4 and 12 days at 30 °C. The BC membranes produced were purified, neutralized and dried at 170 ºC and analyzed by Fourier transform infrared spectroscopy, thermogravimetry, mechanical tests, water absorption capacity, scanning electron microscopy, degree of polymerization and X-ray diffraction. The alternative medium proved to be more advantageous for obtaining BC membranes than the synthetic medium itself, allowing equivalent or superior production and productivity results. The highest BC production was obtained with K. xylinus ATCC 53582, with equivalent results in MRC (3.1 g.L-1) and MHS (3 g.L-1). K. hansenii ATCC 23769 and K. xylinus ARS B42 showed a similar production profile, with MRC (0.63 and 0.88 g.L-1) higher than MHS (0.31 and 0.46 g.L-1). In general, BC productivity decreased after half of the cultivation time, while yields in relation to substrate consumption varied between 2 and 45%. The use of the alternative medium contributed positively to the thermal, physical and structural properties of BC. MRC allows the production of BC with high water absorption capacity when compared to MHS. Despite the lower production obtained in the MRC, the BC from K. xylinus ARS B42 showed high thermal resistance (up to 296.9 ºC) and excellent retention capacity (14864 %), absorbing up to 285 % more water than the BC from the overproducer strain, peculiar characteristic of biopolymer superabsorbent, with high performance for application in dressings, probiotics, cosmetics, packaging, medicines and other industrial processes.